The relationship between mother's behavior in implementing personal hygiene and family environmental sanitation with worm infections in toddlers in Empang Village - Mufida Dwi Agusti; Devi Savitri Effendy; Fifi Nirmala G (PT WIM Solusi Prima, 2026)
Worm infection remains a public health problem among toddlers in areas with inadequate environmental sanitation and suboptimal family hygiene practices. Toddlers are vulnerable due to their habit of playing in the dirt and the mother's independence in maintaining cleanliness. This study aims to determine the relationship between maternal behavior in implementing personal hygiene and family environmental sanitation with worm infection in toddlers. Using a cross-sectional analytical observational design with a sample of 43 mothers and toddlers (purposive sampling). Data on maternal behavior were collected through questionnaires, environmental observations, and detection of worm infection through toddler stool examination using the Kato-Katz method at the Dr. LM Baharuddin Regional Hospital Laboratory. The results showed that most mothers had good personal hygiene behavior (93.0%), healthy environmental sanitation (48.8%), and unhealthy (51.2%). Worm infection occurred in 1 toddler (2.3%). Bivariate analysis found a significant relationship between maternal personal hygiene behavior and worm infection (p=0.232), but not significant for environmental sanitation (p=1.000). It was concluded that maternal personal hygiene practices were significantly associated with worm infections in toddlers, while environmental sanitation was not. Improved health education for mothers and routine screening for worm infections are recommended.